2021
DOI: 10.3389/fnins.2021.654078
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology of Zika Virus: New Models, New Challenges

Abstract: The Zika virus (ZIKV) attracted attention due to one striking characteristic: the ability to cross the placental barrier and infect the fetus, possibly causing severe neurodevelopmental disruptions included in the Congenital Zika Syndrome (CZS). Few years after the epidemic, the CZS incidence has begun to decline. However, how ZIKV causes a diversity of outcomes is far from being understood. This is probably driven by a chain of complex events that relies on the interaction between ZIKV and environmental and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 143 publications
(253 reference statements)
0
4
0
Order By: Relevance
“…The plethora of congenital pathologic lesions usually precipitate devastating neuropathology including microcephaly, cognitive development due to cerebral hypoplasia, and blindness ( 81 83 ). In our study, we were able to mimic microcephaly syndrome with a smaller head circumference, overall brain hypoplasia and consequent neuronal syndromes similar to that seen in humans ( 9 ). Our model is unique in that we were able to document the neurological effects of ZIKV postnatally to determine how the virus elicits CZS.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The plethora of congenital pathologic lesions usually precipitate devastating neuropathology including microcephaly, cognitive development due to cerebral hypoplasia, and blindness ( 81 83 ). In our study, we were able to mimic microcephaly syndrome with a smaller head circumference, overall brain hypoplasia and consequent neuronal syndromes similar to that seen in humans ( 9 ). Our model is unique in that we were able to document the neurological effects of ZIKV postnatally to determine how the virus elicits CZS.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, infants with congenital Zika infection have presented with a high rate of ocular abnormalities due to retinal lesions, chorioretinal atrophy, and optic nerve abnormalities ( 6 , 7 ). The constellation of symptoms due to ZIKV infection that include microcephaly, neuromotor deficits, epileptic seizures, tremors, calcifications, and arthrogryposis are now collectively known as congenital Zika syndrome (CZS) ( 8 , 9 ). Many of these children that have developed CZS from in utero exposure will suffer lifelong long-term effects of severe intellectual disability resulting in significant financial burdens ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence that ZIKV abrogates neurogenesis was provided by Garcez et al [24], who reported a reduced viability and growth of human iPSC-derived NSCs cultured as neurospheres and organoids. An additional study also hypothesized that ZIKV induces a programmed neural cell death, thus causing the disruption of crucial events of early embryonic neurodevelopment [78]. Programmed cell death is essential during morphogenesis, since it helps sculpt brain development.…”
Section: Zika and Nscs/npcsmentioning
confidence: 99%
“…An interesting observation from in vitro studies is that several cells could be the target of ZIKV. While studies in human iPSC-derived neural cells have highlighted the widespread infection and apoptosis of NPCs [78], other studies have indicated that more mature cells, including neurons, radial glial cells, and astrocytes can also be the target [81,82]. Interestingly, radial glia and astrocytes were reported to be more susceptible to infection than neurons [16], because ZIKV replicates more efficiently in undifferentiated compared to differentiated cells [83].…”
Section: Zika and Nscs/npcsmentioning
confidence: 99%